Protein redox chemistry: post-translational cysteine modifications that regulate signal transduction and drug pharmacology - Wani, Revati; Nagata, Asako; Murray, Brion W. (Frontiers in Pharmacology, 2014)
The perception of reactive oxygen species (ROS) has evolved over the past decade from agents of cellular damage to secondary messengers which modify signaling proteins in physiology and the disease state (e.g. cancer). New protein targets of specific oxidation are rapidly being identified. One emerging class of redox modification occurs to the thiol side chain of cysteine residues which can produce multiple chemically-distinct alterations to the protein (e.g. sulfenic/sulfinic/sulfonic acid, disulfides). These post-translational modifications (PTM) are shown to affect the protein structure and function. Because redox-sensitive proteins can traffic between subcellular compartments that have different redox environments, cysteine oxidation enables a spatio-temporal control to signaling. Understanding ramifications of these oxidative modifications to the functions of signaling proteins is crucial for understanding cellular regulation as well as for informed-drug discovery process. The effects of EGFR oxidation of Cys797 on inhibitor pharmacology are presented to illustrate the principle. Taken together, cysteine redox PTM can impact both cell biology and drug pharmacology.